Determinación de la incidencia de Fasciola Hepática en bovinos faenados en el camal municipal del cantón Montalvo, Provincia de Los Ríos - Sánchez Iza, Robinson Adrián (2023)
The present investigation was carried out in the Municipal Camal of the Montalvo Canton belonging to the province of Los Ríos, in the months of August and September 2023. The purpose of the study was to determine the incidence of Fasciola hepatica in cattle slaughtered in the municipal chamber. The sample size was 120 cattle and the variables that were considered were; breed, sex, age and origin of the animals. For the analysis of the data obtained, the percentage method was used with the use of the Microsoft Excel program for tabulation and graphical representation of the results. The samples were obtained using the post-mortem inspection technique. Of the 120 cases sampled, there were no positive cases, therefore an incidence of the disease of 0% was obtained. Regarding the sex variable, 61 females (50.83%) and 59 males (49.17%) were identified, of which there were no positive cases, giving a total of 0%. In the age variable, 32 cattle (26.7%) were found to be 1-3 years old, 52 cattle (43.33%) were 3-5 years old, and 36 cattle (30.0%) were 5-8 years old, of which 0% positive cases were evident. In the breed evaluation, 10 cases of the Brahman breed (8.33%), 11 cases of Holstein Friesian (9.17%), 8 Angus (6.67%) and 91 mixed breeds (75.83%) were studied. , having an incidence of 0% in this variable since there were no positive cases for Fasciola hepatica. In terms of origin, the largest number of slaughtered cattle came from the San Miguel canton with 48 (40.0%), followed by Caluma with a total of 34 cattle (28.33%), then Montalvo with 27 cattle (22.50%). ) and finally Chimbo with 11 cattle (9.17%). Where no positive cases were recorded, giving a 0% incidence. Because no positive cases were evident, it cannot be concerned whether there was a relationship between the incidence of Fasciola hepatica and the variables studied in this research.